Bespoke microbiome therapy to manage plant diseases - Gopal, Murali; Gupta, Alka; Thomas, George V. (Frontiers in Microbiology, 2013)
Advanced biological technologies are revealing that the microbiome, located in gut and rhizosphere, is responsible for maintaining the health of human beings and plants, respectively. Within the complete microbiome a ‘core-microbiome’ exists that plays the pivotal role. Recent studies in medicine have shown that an artificial mixture of bacteria representing the core gut microbiome of healthy person when transferred into gut of diseased person results in re-establishment of normal microflora in the latter leading to alleviation from diseased condition. In agriculture, plant disease management has been achieved through transfer of microbiome by mixing disease suppressive soils with disease conducive soils. However, the exact practice of transferring artificially cultivated core-microbiome as in medicine has not thus far been attempted in plant disease management. Nonetheless, as the gut and rhizosphere microbiome are known to share many common traits, there exists a good scope for accomplishing similar studies in agriculture. Based upon the information in microbiome studies of gut and rhizosphere, we propose that tailor-made core-microbiome transfer therapy can become a viable strategy for management of plant diseases in future.